Population Genetic Analysis of the Rice Stem Borer, Chilo suppressalis, in the South China - Yu-di LIU; Mao-lin HOU; Yu-chun WU; Gui-qin LIU (Journal of Integrative Agriculture, 2013)
Genetic variation and patterns of genetic differentiation of the rice stem borer, Chilo suppressalis (Lepidoptera: Pyralidae), from the South China were analyzed using 6 microsatellite markers and two partial mtDNA (cox1 and cox2) regions. All of the 6 microsatellite loci were polymorphic in the studied seven populations. The allelic richness per population ranged between 5.67 and 14.00, and average HE and HO values were 0.6246-0.8329 and 0.2634-0.6061, respectively. As the mitochondrial genome is a single genetic locus, we only present results for the concatenated data set (cox1 plus cox2 gene sequences, 513 bp). The concatenated data showed high level of genetic diversity and there are 23 variable polymorphic sites among the 513 sites in concatenated data. Nearly all of (20 of 21) pairwise FST comparisons among populations showed genetic differentiation with moderate to high pairwise FST values based on microsatellite markers. However, for the mtDNA data, most of the seven populations did not show significant differentiation with other populations. The differences of population differentiation obtained with the two different genetic markers could be mainly attributed to the different mutation rates of microsatellite and mtDNA. There was not genetic structure existed in these studied populations based on microsatellite loci and mtDNA data. The analysis based on network, mismatch distribution, Tajima's D and FS indicated that the studied populations were from the recent same ancestor or the same refuge and followed by a sudden demographic expansion condition.